Value of the Petromeatal Angle in Predicting Outcome of Translabyrinthine Resection of Vestibular Schwannomas. Issue 4 (29th April 2020) - Noureldine, Mohammad Hassan A; Aum, David; Piper, Keaton; Zavadskiy, Gleb; Peto, Ivo; Bach, Konrad; van Loveren, Harry; Agazzi, Siviero
Abstract: BACKGROUND: Factors associated with extent of tumor resection (EOR) and facial nerve outcomes include tumor size, anterior extension of the tumor, patient age, and surgical approach. OBJECTIVE: To check whether preoperative measurement of the petromeatal (PMA), petroclival (PCA), and petrous-petrous (PPA) angles can help in predicting EOR, facial nerve outcome, and cerebrospinal fluid (CSF) leak occurrence in patients undergoing vestibular schwannoma (VS) surgery via the translabyrinthine approach (TLA). METHODS: A total of 75 patients were included in this retrospective study. Preoperative magnetic resonance imaging constructive interface in steady state and postcontrast T1-weighted sequences through the internal acoustic meatus were used to measure the PMA, PCA, and PPA. RESULTS: There was a statistically significant association between tumor size and EOR; every additional cm in tumor size decreases the odds of gross-total (GTR)/near-total (NTR) resection by 524% ( P  = .0000355). After controlling for tumor size, the logistic models revealed a significant effect of the angles on EOR. For example, in a patient with a 2-cm VS, every additional degree in PMA, PCA, and PPA increases the odds of GTR/NTR by 2.3% ( P  = .0000571), 4.05% ( P  = .0000397), and 0.37% ( P  = .0000438), respectively. After adjusting for tumor size, sex, and age, the effect of PMA on the occurrence of an immediate postoperative facial nerve deficit and CSF leak indicated a trend towards significance ( P  = .0581 and P  = .0568, respectively). CONCLUSION: More obtuse petrous bone angles, namely PMA, PCA, and PPA, are good predictors of GTR or NTR in patients undergoing VS surgery via TLA and may be associated with better facial nerve outcomes and lower CSF leak occurrences.